Occurrence of mycotoxigenic fungi and multi-mycotoxin contamination in corn-based poultry feed supply chain - Nasaruddin, Norafidah (2020)
Corn, a main feed ingredient in the livestock industry, is one of the most susceptible crops to fungal infection and mycotoxin contamination which may occur at any point along the feed supply chain. Most mycotoxins are chemically stable and may be carried over into meat and eggs when poultry are fed with contaminated feed. As compared to individual effects, previous studies suggested that co-occurrence of mycotoxins may have potentially synergistic toxicological effects. Despite the health risks associated with the occurrence of these mycotoxins, no study on occurrence of multi-mycotoxin contamination along the corn-based poultry feed supply chain in Malaysia has been reported. The objectives of this study were therefore to examine the occurrence of mycotoxigenic fungi and aflatoxin contamination. The occurrence of multimycotoxin contamination along corn-based poultry feed supply chain was also determined. A total of 51 samples were collected from different points along the feed supply chain from two integrated poultry feed companies. The samples were subjected to mycological analyses (fungal isolation, enumeration, identification), and aflatoxins were quantified by high performance liquid chromatography equipped with fluorescence detector (HPLC-FLD). The samples were then analyzed by liquid chromatography-tandem mass spectrometry (LC-MS/MS) to determine the occurrence of other mycotoxins. The results showed that samples collected from sampling point 1 (company A) and sampling point 9 (company B) yielded the highest total fungal loads (> log 4 CFU/g). The prevalent fungal genera isolated were Aspergillus (43.1%), Fusarium (52.9%), and Penicillium spp. (41.2%). Aflatoxin B1 was detected in 8.3% of corn samples (0.12 – 1.51 μg/kg) and 7.4% of corn-based poultry feed (0.23 – 0.63 μg/kg) samples along the feed supply chain, whereas aflatoxins B2, G1, and G2 were not detected. Results from LC-MS/MS analysis revealed that 100% of samples along the corn-based poultry feed supply chain were contaminated with more than one mycotoxin. Fumonisin B1 (8.02 – 1,220.33 μg/kg) and fumonisin B2 (11.05 – 1,108.67 μg/kg) were the main mycotoxins detected at all sampling points along the feed supply chain. Zearalenone (ZEA) (2.57 – 7.50 μg/kg) and HT-2 (< LOD – 32.90 μg/kg) were also detected in 17.65% (n = 9) and 52.94% (n = 27) (out of a total of 51) samples, respectively. As the supply chain progresses, reduction in mycotoxin contamination was observed. Aflatoxins, ochratoxin A (OTA), deoxynivalenol (DON) and T-2 toxin were also detected, but at very low levels (< LOD). The levels of mycotoxins detected along the supply chain were below the international regulatory limits, thus indicating that the risk level of exposure to mycotoxins along the corn-based poultry feed supply chain in Malaysia is very low. However, due to the composition of multiple ingredients in most food and feed, efforts to understand and address challenges associated with mycotoxins along the entire supply chain need to be more holistic to protect the public health.